Biosurfactants on area measurement plastic articles

By using biosurfactants to treat plastic products, the problem of cracking in plastic products under surfactant conditions is solved, achieving the effect of reducing cracking and signs of aging, while providing excellent cleaning performance and low toxicity.

CN120813671APending Publication Date: 2025-10-17EVONIK OPERATIONS GMBH
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
CN202480019127.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-16
Filing Date
2024-03-11
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Plastic products are prone to environmental stress cracking (ESC) when exposed to surfactants for a long time, and existing technologies are difficult to effectively prevent or reduce this phenomenon.

Method used

Treating plastic products with biosurfactants such as rhamnolipin, sophorolipid, and glucose lipolipin reduces environmental stress cracking and signs of aging by contacting and optionally removing a portion of the liquid composition.

Benefits of technology

Biosurfactants have shown excellent performance in reducing and preventing environmental stress cracking, while providing good foaming ability, skin compatibility and low aquatic toxicity, and can effectively clean at low temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to biosurfactants on area measurement plastic articles and to the use thereof, in particular in a clean context.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the invention

[0001] The present invention relates to a biosurfactant on area measuring plastic articles and uses thereof, especially in the context of cleaning. State of the art

[0002] Plastics are a wide range of synthetic or semi-synthetic materials that use polymers as the main ingredient. Their plasticity allows plastics to be molded, extruded or pressed into various shapes of solid objects.

[0003] Plastics are generally considered to be stable to many environmental influences and have a slow rate of decomposition in nature.

[0004] However, plastics do suffer from the influence of surfactants, for example by long time exposure or repeated cleaning procedures when using surfactants. This phenomenon is called environmental stress cracking (ESC), for example, Kawaguchi et al. in Polymer Engineering and Science, Vol. 43, No. 2, pp. 419-430, Environmental stress cracking (ESC) of plastics caused by non-ionic surfactants are compared.

[0005] In order to use plastic articles sustainably, it is therefore desirable to prevent ESC of the articles.

[0006] It is an object of the present invention to provide a method of handling plastics that reduces the influence of stresses applied on the plastics. SUMMARY

[0007] Surprisingly, it was found that biosurfactants can solve the problem of the present invention.

[0008] The present invention thus provides a method of handling area measuring plastic articles when using a biosurfactant.

[0009] It is an advantage of the present invention that the liquid composition used in the present invention foams strongly, i.e. a large amount of foam is generated.

[0010] It is a further advantage of the present invention that the liquid composition used in the present invention generates a foam that is still stable over time.

[0011] It is a further advantage of the present invention that the liquid composition used in the present invention has a good initial foaming behavior.

[0012] It is a further advantage of the present invention that the liquid composition used in the present invention has a good skin compatibility.

[0013] It is a further advantage of the present invention that the liquid composition used in the present invention has a good run-off behavior.

[0014] Another advantage of the present application is that the liquid compositions used in the present application have a good drying behavior.

[0015] Another advantage of the present application is that the liquid compositions used in the present application also show excellent foam building capacity in the presence of oil stains.

[0016] Another advantage of the present application is that strong foam building formulations can be formulated without the need to use surfactants prepared with ethylene oxide.

[0017] Another advantage is the reduced need for microbiologically active preservatives.

[0018] Another advantage of the liquid compositions used in the present application is that they have a low viscosity and are therefore simple to process in any desired aqueous surfactant system.

[0019] Another advantage of the liquid compositions used in the present application is that they have a very good solubilizing efficacy for essential oils at low use levels.

[0020] Another advantage of the liquid compositions used in the present application is that they are mild and have a good physiological compatibility.

[0021] Another advantage of the liquid compositions used in the present application is that they have a good rinsability compared to other surfactant compositions.

[0022] Another advantage of the liquid compositions used in the present application is that they can be synthesized without the use of petrochemical-based raw materials.

[0023] Another advantage of the liquid compositions used in the present application is that they can be synthesized without the use of critical raw materials such as tropical oils.

[0024] Another advantage of the liquid compositions used in the present application is their excellent microbiological stability.

[0025] Another advantage of the liquid compositions used in the present application is that a particularly good foam creaminess can be achieved.

[0026] Another advantage of the present application is that the liquid compositions used in the present application can be rinsed off very easily from surfaces, preferably from fibers that have already been cleaned.

[0027] Another advantage is that the liquid compositions used in the present application support the stability of enzymes in storage.

[0028] Another advantage is that the liquid compositions used in the present application support the stability of probiotic bacteria in storage.

[0029] Another advantage of the present invention is that the liquid composition used in the present invention exhibits particularly good emulsifying and dispersing properties.

[0030] Another advantage of the present invention is that the liquid composition used in the present invention has low aquatic toxicity.

[0031] Another advantage of the present invention is that the liquid composition used in the present invention can be formulated to be 100% biodegradable.

[0032] Another advantage is that the liquid composition used in the present invention can be very easily diluted with water without the need for excessive agitation.

[0033] An advantage of the present invention is that the liquid composition used in the present invention has a positive odor profile.

[0034] Another advantage of the present invention is that the liquid composition used in the present invention has improved color stability.

[0035] Another advantage is that the liquid composition used in the present invention has improved surface cleaning properties, especially for fatty stains.

[0036] Another advantage is that the liquid composition used in the present invention has excellent foaming properties.

[0037] Another advantage is that the liquid composition used in the present invention has reduced skin irritation to human skin.

[0038] Another advantage is that the liquid composition used in the present invention has mildness and good physiological compatibility, in particular characterized by high values in the red blood cell (RBC) test.

[0039] Another advantage is that the liquid composition used in the present invention has good skin feel during and after cleaning.

[0040] Another advantage is that the liquid composition used in the present invention has improved ability to dissolve oils and fats.

[0041] Another advantage is that the liquid composition used in the present invention is more easily removed from surfaces and thus requires less water for the rinsing step.

[0042] Another advantage is that the liquid composition used in the present invention provides the benefit of streak-free cleaning when used to clean glass, mirrors, windshields, and other sensitive surfaces.

[0043] Another advantage is that the liquid composition used in the present invention can effectively clean even at lower temperatures.

[0044] Thus, the present invention provides a method of handling area-measuring plastic articles, comprising the steps of A) providing a liquid composition comprising a biosurfactant, and contacting the article with the liquid composition, and optionally B) at least partially removing the liquid composition comprising the biosurfactant from the article.

[0045] In the context of the present invention, "biosurfactant" is understood to mean all glycolipids produced by fermentation. The term "biosurfactant" also encompasses glycolipids which have been modified chemically or enzymatically after fermentation, as long as the glycolipid is structurally retained.

[0046] Raw materials which can be used for the preparation of the biosurfactant are carbohydrates, in particular sugars, such as, for example, glucose and / or lipophilic carbon sources, such as fats, oils, partial glycerides, fatty acids, fatty alcohols, long-chain saturated or unsaturated hydrocarbons.

[0047] In the context of the present invention, the term "surfactant" is understood to mean an organic substance which has interfacial active properties, which has the ability to reduce the surface tension of water to below 45 mN / m at 20°C and at a concentration of 0.5% by weight, based on the total composition. The surface tension is determined by the Du Noüy ring method at 20°C.

[0048] In the context of the present invention, the term "liquid" is understood to mean a liquid at a temperature of 25°C and a pressure of 1013 mbar.

[0049] In the case where average values are stated hereinafter, these are number average values, unless stated otherwise.

[0050] Percentages are data in percent by weight, unless stated otherwise.

[0051] In the case where measurement values are stated hereinafter, these are determined at a temperature of 25°C and a pressure of 1013 mbar, unless stated otherwise.

[0052] The method according to the present invention is preferably a method for impregnating, servicing and cleaning, in particular cleaning, the plastic article.

[0053] Preferably, the method according to the present invention is a method for servicing the plastic article in terms of reducing and / or preventing environmental stress cracking, preferably caused by at least one non-biosurfactant, and / or reducing signs of aging, preferably caused by at least one non-biosurfactant.

[0054] The article of the method of the present invention is an area-measuring article, but not a textile or cloth.

[0055] The article of manufacture of the method of the present application is preferably a hard surface article. The article is preferably selected from the group consisting of tiles, shelves, panels, furniture, pump housings, pump wheels, bull's eyes of washing machines, racks and holders of dishwashers, food processing equipment, washing machines, dishwashers, car cleaning equipment, car related surfaces, train related surfaces, laminates, ceramic coated articles and metals, steel (especially steel of the stainless steel grade), aluminum alloys and enamel steel.

[0056] According to the method of the present application, preferably, it is characterized in that the plastic article comprises a polymer selected from the group consisting of acrylics, especially methacrylates and methyl methacrylate, polyamides, polyesters, silicones and polyurethanes, polycarbonates, polyethylenes, polypropylenes, polystyrenes, polyvinyl chlorides and polyformals, preferably a polymer selected from the group consisting of polycarbonates, polystyrenes and methyl methacrylate, more preferably a polymer selected from the group consisting of acrylonitrile butadiene styrene, polycarbonate and polymethyl methacrylate.

[0057] According to the method of the present application, preferably, it is characterized in that the biosurfactant is selected from the group consisting of rhamnolipids, sophorolipids, glucolipids, cellulose lipids, mannosylerythritol lipids and trehalose lipids, preferably rhamnolipids, sophorolipids and glucolipids, most preferably rhamnolipids.

[0058] Of course, mixtures of different biosurfactants can be comprised in the liquid composition.

[0059] The biosurfactant can be prepared, for example, according to EP 0 499 434, US 7,985,722, WO 03 / 006146, DE 19648439, DE 19600743, JP 01 304034, CN 1337439, JP 2006 274233, JP 2006083238, JP 2006 070231, WO 03 / 002700, FR 2740779, DE 2939519, US 7,556,654, FR 2855752, EP 1445302, JP 2008 062179 and JP 2007 181789 or documents cited therein. Suitable biosurfactants can be obtained, for example, from Soliance, France.

[0060] Preferably, according to the method of the present application, preferably, it is characterized in that the biosurfactant is selected from the group consisting of rhamnolipids, especially mono-, di- or poly-rhamnolipids, glucolipids, especially mono-, di- or poly-glucolipids, and sophorolipids, especially mono-, di- or poly-sophorolipids, preferably from the group consisting of rhamnolipids and glucolipids, most preferably rhamnolipids.

[0061] The term "rhamnolipid" is preferably understood in the context of the present application to mean in particular a compound of the general formula (I) Formula (I) wherein mRL = 2, 1 or 0, preferably 1 or 0, nRL = 1 or 0, R 1RL and R 2RL = independently of one another identical or different organic residues having 2 to 24 carbon atoms, preferably 5 to 13 carbon atoms, in particular optionally branched, optionally substituted, in particular hydroxyl-substituted, optionally unsaturated, in particular optionally mono-, di- or tri-unsaturated alkyl residues, preferably selected from the group consisting of pentenyl, heptenyl, nonenyl, undecenyl and tridecenyl and (CH2) o -CH3, wherein o = 1 to 23, preferably 4 to 12.

[0062] If nRL = 1, the glycosidic bond between the two rhamnose units is preferably in the alpha-configuration. The optically active carbon atom of the fatty acid is preferably present as the R-enantiomer (e.g. (R)-3-{(R)-3-[2-O-(alpha-L- rhamnopyranosyl)-alpha-L-rhamnopyranosyl]oxydecanoyl}oxydecanoate).

[0063] The term "di-rhamnolipid" is understood in the context of the present application to mean a compound of the general formula (I) or a salt thereof, wherein nRL = 1.

[0064] The term "mono-rhamnolipid" is understood in the context of the present application to mean a compound of the general formula (I) or a salt thereof, wherein nRL = 0.

[0065] Different rhamnolipids are abbreviated according to the following nomenclature: "diRL-CXCY" is understood to mean a di-rhamnolipid of the general formula (I), wherein one of the residues R 1RL and R 2RL = (CH2) o -CH3, wherein o = X-4, and the remaining residues R 1 or R 2 = (CH2) o -CH3, wherein o = Y-4.

[0066] "monoRL-CXCY" is understood to mean a mono-rhamnolipid of the general formula (I), wherein one of the residues R 1RL and R 2RL = (CH2) o -CH3, wherein o = X-4, and the remaining residues R1RL or R 2RL = (CH2) o -CH3, where o = Y-4.

[0067] Therefore, the nomenclature used does not distinguish between "CXCY" and "CYCX".

[0068] For rhamnolipids where mRL = 0, monoRL-CX or diRL-CX was used accordingly.

[0069] If one of the above symbols X and / or Y is accompanied by ":Z", this means that the corresponding residue R 1RL and / or R 2RL Equivalent to an unbranched, unsubstituted hydrocarbon residue having X-3 or Y-3 carbon atoms with Z double bonds.

[0070] Methods for preparing related rhamnolipids are disclosed in, for example, EP2786743 and EP2787065.

[0071] Background applicable to the present invention Rhamnolipids can also be produced by Pseudomonas species, especially Pseudomonas aeruginosa ( Pseudomonas aeruginosa ), preferably non-genetically modified Pseudomonas aeruginosa cells, a technique already known in the 1980s, as described in, for example, EP 0 282 942 and DE 4 1 27 908. Rhamnolipids produced in Pseudomonas aeruginosa cells that have been genetically modified for higher rhamnolipid titers can also be used in the context of the present invention; for example, Lei et al. disclose such cells in Biotechnol Lett. 2020 Jun; 42(6): 997-1002.

[0072] Rhamnolipids produced by Pseudomonas aeruginosa are commercially available from Jeneil Biotech Inc., for example, under the trade name Zonix, from Logos Technologies (technology acquired by Stepan), for example, under the trade name NatSurFac, from Biotensidion GmbH, for example, under the trade name Rhapynal, from AGAE technologies, for example, under the names R90, R95, R95Md, R95Dd, from Locus Bio-Energy Solutions, and from Shanghai Yusheng Industry Co. Ltd., for example, under the trade name Bio-201 Glycolipids.

[0073] The present invention provides a method of preferably including a rhamnolipid as the biosurfactant in the liquid composition, characterized in that the rhamnolipid comprises 51 to 100 wt.%, preferably 60 to 95 wt.%, particularly preferably 80 to 90 wt.% of mono-rhamnolipids, especially those of formula (I) wherein nRL=0, wherein the weight percentages are referred to the sum of all rhamnolipids contained in the liquid composition.

[0074] The present application provides a method for preferably comprising in said liquid composition rhamnolipids as said biosurfactant, characterized in that said rhamnolipids comprise 71 to 100 wt.%, preferably 75 to 95 wt.%, particularly preferably 80 to 90 wt.% of di-rhamnolipids, especially those of formula (I) wherein nRL=1, wherein the weight percentages are referred to the sum of all rhamnolipids contained in the liquid composition.

[0075] The present application further provides a method for preferably comprising in said liquid composition rhamnolipids as said biosurfactant, characterized in that said rhamnolipids comprise 56 to 95 wt.%, preferably 60 to 80 wt.%, particularly preferably 66 to 70 wt.% of diRL-C10C10, wherein the weight percentages are referred to the sum of all rhamnolipids contained in the liquid composition.

[0076] According to a preferred method of the present application, characterized in that the biosurfactant contained in said liquid composition is said rhamnolipid as described above, in an amount of 0.5 to 15 wt.%, preferably 3 to 12 wt.%, particularly preferably 5 to 10 wt.% of diRL-C10C12:1, wherein the weight percentages are referred to the sum of all rhamnolipids contained in the liquid composition.

[0077] According to another preferred method of the present application, characterized in that the biosurfactant contained in said liquid composition is said rhamnolipid as described above, in an amount of 0.5 to 25 wt.%, preferably 3 to 15 wt.%, particularly preferably 5 to 12 wt.% of diRL-C10C12, wherein the weight percentages are referred to the sum of all rhamnolipids contained in the liquid composition.

[0078] According to a preferred method of the present application, characterized in that the biosurfactant contained in said liquid composition is said rhamnolipid as described above, in an amount of 0.1 to 25 wt.%, preferably 2 to 10 wt.%, particularly preferably 4 to 8 wt.% diRL-C8C10, wherein the weight percentages refer to the sum of all rhamnolipids contained in the liquid composition.

[0079] According to an even further preferred method according to the present application, characterized in that the biosurfactant contained in the liquid composition is the rhamnolipid as described above, in an amount of 0.1 to 5 wt.%, preferably 0.5 to 3 wt.%, particularly preferably 0.5 to 2 wt.% monoRL-C8C10 and / or, preferably and 0.1 to 5 wt.%, preferably 0.5 to 3 wt.%, particularly preferably 0.5 to 2 wt.% monoRL-C10C10, wherein the weight percentages refer to the sum of all rhamnolipids contained in the liquid composition.

[0080] The present application provides an alternative method, preferably comprising in the liquid composition as the biosurfactant rhamnolipids, characterized in that the rhamnolipids comprise 10 to 30 wt.%, preferably 20 to 30 wt.%, particularly preferably 25 to 30 wt.% monoRL-C10C10, wherein the weight percentages refer to the sum of all rhamnolipids contained in the liquid composition.

[0081] According to an alternative preferred method according to the present application, characterized in that the biosurfactant contained in the liquid composition is the rhamnolipid as described above, in an amount of 10 to 30 wt.%, preferably 12 to 25 wt.%, particularly preferably 15 to 20 wt.% diRL-C10C10, wherein the weight percentages refer to the sum of all rhamnolipids contained in the liquid composition.

[0082] According to an alternative preferred method according to the present application, characterized in that the biosurfactant contained in the liquid composition is the rhamnolipid as described above, in an amount of 10 to 30 wt.%, preferably 12 to 25 wt.%, particularly preferably 15 to 20 wt.% monoRL-C8C10, wherein the weight percentages refer to the sum of all rhamnolipids contained in the liquid composition.

[0083] According to an alternative preferred method of the present application, the biosurfactant comprised in the liquid composition is the rhamnolipid as described above, in an amount of 3 to 25 wt%, preferably 5 to 20 wt%, in particular preferably 10 to 15 wt% of monoRL-C10C12:1, wherein the weight percentages are referred to the sum of all rhamnolipids comprised in the liquid composition.

[0084] According to an alternative preferred method of the present application, the biosurfactant comprised in the liquid composition is the rhamnolipid as described above, in an amount of 1 to 15 wt%, preferably 2 to 10 wt%, in particular preferably 3 to 8 wt% of diRL-C10C12, wherein the weight percentages are referred to the sum of all rhamnolipids comprised in the liquid composition.

[0085] Methods for the preparation of the relevant rhamnolipids are disclosed, for example, in EP2786743 and EP2787065.

[0086] Rhamnolipids suitable for use in the context of the present application can also be produced by fermentation of Pseudomonas, in particular Pseudomonas aeruginosa, which is preferably a non-genetically modified cell, a technology which has been disclosed already in the 80s, as documented, for example, in EP0282942 and DE4127908. Rhamnolipids produced in Pseudomonas aeruginosa cells which have been improved by genetic modification for higher rhamnolipid titers can also be used in the context of the present application; such cells are disclosed, for example, by Lei et al. in Biotechnol Lett. 2020 Jun; 42(6): 997-1002.

[0087] Rhamnolipids produced by Pseudomonas aeruginosa are commercially available from Jeneil Biotech Inc., for example under the tradename Zonix, from Logos Technologies (technology acquired by Stepan), for example under the tradename NatSurFac, from Biotensidion GmbH, for example under the tradename Rhapynal, from AGAE technologies, for example under the names R90, R95, R95Md, R95Dd, from Locus Bio-Energy Solutions and from Shanghai Yusheng Industry Co. Ltd., for example under the tradename Bio-201 Glycolipids.

[0088] In the context of the present invention, the term "sophorolipid" is preferably understood to mean compounds of the general formula (IIa) and (IIb) and their salts Formula (IIa) Formula (IIb) in R 1SL = H or CO-CH3, R 2SL = H or CO-CH3, R 3SL = a divalent organic moiety comprising 6 to 32 carbon atoms and which is unsubstituted or substituted by hydroxyl functions, which is unbranched and optionally comprises 1 to 3 double or triple bonds, R 4SL = H, CH 3 or a monovalent organic group which contains 2 to 10 carbon atoms and which is unsubstituted or substituted by hydroxy functions, which is unbranched and which optionally contains 1 to 3 double or triple bonds, and nSL = 1 or 0.

[0089] Sophorolipids can be used according to the invention in their acid form or in their lactone form.

[0090] Preferred compositions according to the invention comprise sophorolipids in which the weight ratio of lactone form to acid form is from 20:80 to 80:20, particularly preferably from 30:70 to 40:60.

[0091] For determining the content of sophorolipids in the acid or lactone form in the formulations, reference is made to EP 1 411 111 B1 , page 8, paragraph

[0053] .

[0092] In connection with the present invention, the term "glucose lipids" is preferably understood to mean compounds of the general formula (III) and their salts, Formula (III) in mGL=3, 2, 1 or 0, preferably 1 or 0, R 1GL and R 2GL = independently of one another are identical or different organic radicals having 2 to 24 carbon atoms, in particular optionally branched, optionally substituted, in particular hydroxy-substituted, optionally unsaturated, in particular optionally mono-, di- or triunsaturated alkyl radicals, preferably selected from the group consisting of pentenyl, heptenyl, nonenyl, undecenyl and tridecenyl and (CH2) o -CH3 group, wherein o = 1 to 23, preferably 4 to 12.

[0093] The different glucose lipids are abbreviated according to the following nomenclature: "GL-CXCY" is understood to mean a glucose lipid of the general formula (III), wherein the radicals R 1GL and R 2GL = (CH2) o -CH3, wherein o = X-4, and the remaining radicals R 1GL or R 2GL = (CH2) o -CH3, wherein o = Y-4.

[0094] Thus, the nomenclature used does not distinguish between "CXCY" and "CYCX".

[0095] If one of the above-mentioned designations X and / or Y carries ":Z", this means that the respective radical R 1GL and / or R 2GL = an unbranched, unsubstituted hydrocarbon radical having X-3 or Y-3 carbon atoms with Z double bonds.

[0096] The method for preparing the glucose lipid can be carried out as described in WO2019154970.

[0097] The preferred method according to the present application is characterized in that the liquid composition provided in step A) comprises a non-biological surfactant, preferably selected from the group consisting of anionic, cationic, non-ionic, semi-polar, amphoteric and zwitterionic surfactants, in particular a non-ionic surfactant, more preferably selected from the group consisting of fatty alcohol alkoxylates and alkyl polyglucosides, in particular fatty alcohol ethoxylates.

[0098] It is clear that a non-biological surfactant is different from a biological surfactant as defined in the context of the present application.

[0099] Non-limiting examples of anionic surfactants include sulfates and sulfonates, in particular linear alkylbenzene sulfonates (LAS), isomers of LAS, branched alkylbenzene sulfonates (BABS), phenylalkane sulfonates, alpha-olefin sulfonates (AOS), olefin sulfonates, alkenyl sulfonates, alkane-2,3-diylbis(sulfates), hydroxyalkane sulfonates and disulfonates, alkyl sulfates (AS) such as sodium dodecyl sulfate (SDS), fatty alcohol sulfates (FAS), primary alcohol sulfates (PAS), alkyl ether sulfates (AES or AEOS or FES, also known as alcohol ethoxysulfates or fatty alcohol ether sulfates), secondary alkane sulfonates (SAS), paraffin sulfonates (PS), ester sulfonates, sulfonated fatty acid glycerol esters, alpha-sulfo fatty acid methyl esters (alpha-SFMe or SES), including methyl ester sulfonates (MES), alkyl or alkenyl succinic acids, dodecenyl / tetradecenyl succinic acid (DTSA), fatty acid derivatives of amino acids, diesters and monoesters of sulfosuccinic acid or soap, and combinations thereof.

[0100] Non-limiting examples of cationic surfactants include alkyl dimethyl ethanolamine quaternary ammonium salts (ADMEAQ), cetyltrimethylammonium bromide (CTAB), dimethyldistearylammonium chloride (DSDMAC), and alkylbenzyldimethylammonium, alkyl quaternary ammonium compounds, alkoxylated quaternary ammonium (AQA) compounds, and combinations thereof.

[0101] Non-limiting examples of non-ionic surfactants include fatty alcohol ethoxylates (AE or AEO), which are preferably included in the liquid composition of the present application, alcohol propoxylates, propoxylated fatty alcohols (PFA), alkoxylated fatty acid alkyl esters, such as ethoxylated and / or propoxylated fatty acid alkyl esters, alkyl phenol ethoxylates (APE), nonyl phenol ethoxylates (NPE), alkyl polyglycosides (APG), alkoxylated amines, fatty acid monoethanolamides (FAM), fatty acid diethanolamides (FADA), ethoxylated fatty acid monoethanolamides (EFAM), polyglycerol esters, glycerol esters, propoxylated fatty acid monoethanolamides (PFAM), polyhydroxyalkyl fatty acid amides, or N-acyl N-alkyl derivatives of glucosamine (glucamides, GA, or fatty acid glucamides, FAGA), as well as products available under the trade names SPAN and TWEEN, and combinations thereof.

[0102] Non-limiting examples of semi-polar surfactants include amine oxides (AO), such as alkyl dimethyl amine oxide, N-(cocoalkyl)-N,N-dimethylamine oxide, and N-(tallowalkyl)-N,N-bis(2-hydroxyethyl)amine oxide, fatty acid alkanolamides, and ethoxylated fatty acid alkanolamides, and combinations thereof.

[0103] Non-limiting examples of amphoteric and zwitterionic surfactants include betaines, alkyl dimethyl betaine, sulfobetaine, hydroxysulfobetaine, and combinations thereof.

[0104] In addition, the liquid composition of the present application can include a bio-based surfactant that is not based on glucose lipids, such as a lipopeptide, such as surfactin, or a phospholipid, such as lecithin.

[0105] According to a preferred method of the present application, the liquid composition provided in step A) comprises the biosurfactant in an amount of 0.1 wt.% to 30 wt.%, preferably 0.5 wt.% to 10 wt.%, more preferably 1.0 wt.% to 8 wt.%, wherein the weight percentage is referred to the total liquid composition.

[0106] When determining the content of biosurfactant in the context of the present application, the mass of the non-salt form is considered; thus, the weight of the corresponding cation is ignored.

[0107] According to a preferred method of the present application, it is characterized in that the liquid composition provided in step A) comprises water in an amount of 70 wt.% to 99.9 wt.%, preferably 90 wt.% to 99.5 wt.%, more preferably 92 wt.% to 99.0 wt.%, wherein the weight percent is referred to the total liquid composition.

[0108] According to a preferred method of the present application, it is characterized in that the liquid composition provided in step A) comprises the non-biological surfactant in an amount of 0.1 wt.% to 30 wt.%, preferably 0.5 wt.% to 10 wt.%, more preferably 1.0 wt.% to 8 wt.%, wherein the weight percent is referred to the total liquid composition.

[0109] According to a preferred method of the present application, it is characterized in that the liquid composition provided in step A) comprises the biological surfactant in an amount of 20 wt.% to 100 wt.%, preferably 30 wt.% to 70 wt.%, more preferably 40 wt.% to 60 wt.%, wherein the weight percent is referred to the sum of all surfactants comprised in the liquid composition.

[0110] In step B) of the method of the present application, at least part of the liquid composition comprising the biological surfactant is removed therefrom.

[0111] The removal is preferably performed by draining the liquid composition and rinsing the article, preferably with water.

[0112] The present application further provides the use of a biological surfactant for reducing and / or preventing environmental stress cracking, preferably caused by at least one non-biological surfactant, of an area-measured plastic article.

[0113] The present application further provides the use of a biological surfactant for reducing signs of aging, preferably caused by at least one non-biological surfactant, of an area-measured plastic article, the signs of aging preferably being selected from the group consisting of scratches, surface dullness, uneven gloss, and surface cracking.

[0114] Preferably, the use according to the present application is characterized in that the biological surfactant is selected from the group consisting of rhamnolipids, glucolipids, and sophorolipids, preferably rhamnolipids and glucolipids, most preferably rhamnolipids.

[0115] Preferably, the use according to the present application is characterized in that the non-biological surfactant causing environmental stress cracking and / or signs of aging is selected from the group consisting of anionic, cationic, non-ionic, semi-polar, amphoteric, and zwitterionic surfactants, especially non-ionic surfactants, more preferably from the group consisting of fatty alcohol alkoxylates and alkyl polyglucosides, especially fatty alcohol ethoxylates.

[0116] Preferably, the use according to the present application is characterized in that the biosurfactant is contained in the liquid composition together with the non-biosurfactant.

[0117] In the use according to the present application, the same preferred embodiments in terms of article, biosurfactant, non-biosurfactant, concentration and polymer apply to the method according to the present application as described above.

[0118] The examples cited below illustrate the present application and are not intended to limit the application to the embodiments specified in the examples, the scope of the application being apparent from the entire specification and claims.

[0119] Examples: Example 1 This example demonstrates the compatibility of biosurfactants with plastic materials by examining the extent of environmental stress cracking induced by surfactant solutions on various plastics.

[0120] The material care assessment was carried out according to an in-house test method which was adapted from the recommendations of the German Cosmetic, Toiletry, Perfumery and Detergent Association (IKW): “IKW Recommendation for the Quality Assessment of the Product Performance of All-Purpose Cleaners 2014” (IKW test protocol). The test principle is to assess the environmental stress cracking induced on selected plastic materials after exposure to aqueous surfactant solutions. For the test, four different types of test bars were used which were made of acrylonitrile-butadiene-styrene copolymer, polystyrene, polycarbonate and poly(methyl methacrylate), respectively. On each test bar a hole was drilled (drill 2.7 and reamer 2.9 H7) and a rustproof steel pin (dowel DIN 6325 tolerance designation: m6 3x10) was pressed vertically into each test bar using a device such as a rack and pinion press type 5. Subsequently, the test bars were immersed into the test solution (Table 1) for 30 seconds. After removal of the test bars from the solution, the adhering liquid was not removed and the bars were placed horizontally at room temperature. The process of immersing the bars into the test solution was repeated every 24 hours for five days a week (Monday to Friday) for a period of two weeks. The test bars were assessed every 24 hours for the appearance of stress cracks and recorded. The following plastics were tested: acrylonitrile butadiene styrene copolymer - ABS Galvano Novodur, polycarbonate - Makrolon, poly(methyl methacrylate) - Plexiglas 8N and polystyrene. ABS Galvano Novodur, polycarbonate - Makrolon, poly(methyl methacrylate) - Plexiglas 8N and polystyrene. ABS Galvano Novodur, polycarbonate - Makrolon, poly(methyl methacrylate) - Plexiglas 8N and polystyrene.

[0121] The formulations described in Table 1 were prepared according to the following protocol. First, a measured amount of water was introduced into a glass beaker of appropriate size. Subsequently, the desired amount of surfactant was added at room temperature with vigorous stirring. Finally, any remaining amount of water was introduced to ensure the desired concentration of surfactant. All ingredients were mixed for 5 minutes using a magnetic stirrer to ensure a uniform solution. The exemplary compositions were easy to pour and were stable for a long time at room temperature.

[0122] Rhamnolipids were prepared as described in Example 1 of EP3023431.

[0123] The sophorolipid used was the sophorolipid REWOFERM® SL ONE from Evonik, which has a lactone to acid ratio of 40:60.

[0124] Table 1. Compositions of Test Formulations 1 and 2 and Baseline Formulations 1, 2, and 3 used in Environmental Stress Cracking Testing. Test formulation 1 / % Test formulation 2 / % Reference formulation 1 / % Reference formulation 2 / % Reference formulation 3 / % Rhamnolipid 5.0 0.0 0.0 0.0 0.0 Sophorolipid 0.0 5.0 0.0 0.0 0.0 Linear alkyl benzene sulfonate sodium salt 0.0 0.0 5.0 0.0 0.0 C12-14 fatty alcohol ethoxylate, 6 EO 0.0 0.0 0.0 5.0 0.0 Alkyl polyglucoside 0.0 0.0 0.0 0.0 5.0 Water Added to 100% Added to 100% Added to 100% Added to 100% Added to 100%

[0125] The results for environmental stress cracking are summarized in Table 2. Surprisingly, no stress cracking was observed in the polymethyl methacrylate, polycarbonate, acrylonitrile butadiene styrene, and polystyrene rods when exposed to Test Formulation 1 and Test Formulation 2.

[0126] Exposure to baseline formulation 1 caused environmental stress cracking in polycarbonate and acrylonitrile butadiene styrene, while no cracking was observed in polymethyl methacrylate and polystyrene. Baseline formulation 2 caused environmental stress cracking in all tested plastic materials, while baseline formulation 3 caused environmental stress cracking in polycarbonate samples. No cracking was observed in polymethyl methacrylate, acrylonitrile butadiene styrene, or polystyrene samples upon exposure to baseline formulation 3. Thus, unexpectedly, test formulations 1 and 2 were found to be gentle on plastic materials, as they did not cause environmental stress cracking in common plastics such as polymethyl methacrylate, polycarbonate, acrylonitrile butadiene styrene, and polystyrene under the test conditions.

[0127] Table 2. Environmental stress cracking results after 14 days (Yes - stress cracking was observed after the test was completed, No - stress cracking was not observed after the test was completed) Test formulation 1 Test formulation 2 Reference formulation 1 Reference formulation 2 Reference formulation 3 Polymethyl methacrylate No No No Yes No Polycarbonate No No Yes Yes Yes Acrylonitrile-butadiene-styrene No No Yes Yes No Polystyrene No No No Yes No

[0128] Example 2 This example demonstrates the effectiveness of a mixture of biosurfactants and conventional surfactants by examining the extent of environmental stress cracking induced by surfactant solutions on various plastics.

[0129] The material care assessment was performed according to an in-house test method which was adapted from the German Cosmetic, Toiletry, Perfumery and Detergent Association (IKW): "IKW Recommendation for the Quality Assessment of the Product Performance of All-Purpose Cleaners 2014" (IKW test protocol). The test principle is to assess the environmental stress cracking induced by selected plastic materials after exposure to aqueous surfactant solutions. For the test, four different types of test bars were used which were made of acrylonitrile-butadiene-styrene copolymer, polystyrene, polycarbonate and poly(methyl methacrylate), respectively. On each test bar a hole was drilled (drill 2.7 and reamer 2.9 H7) and a rustproof steel pin (set pin DIN 6325 tolerance designation: m6 3x10) was pressed vertically into each test bar using a device such as a rack and pinion press type 5. Subsequently, the test bars were immersed into the test solution (Table 1) for 30 seconds. After removal of the test bars from the solution, without removing the adhering liquid, the bars were placed horizontally at room temperature. The procedure of immersing the bars into the test solution was repeated every 24 hours for five days a week (Monday to Friday) for a period of two weeks. The test bars were assessed every 24 hours for the appearance of stress cracks and recorded. The following plastics were tested: acrylonitrile butadiene styrene - ABS Galvano Novodur, polycarbonate - Makrolon, poly(methyl methacrylate) - Plexiglas 8N and polystyrene. ABS Galvano Novodur, polycarbonate - Makrolon, poly(methyl methacrylate) - Plexiglas 8N and polystyrene.

[0130] The formulations described in Tables 3 and 4 were prepared according to the following protocol. First, the measured amount of water was introduced into a suitably sized glass beaker. Subsequently, the required amount of surfactant was added at room temperature and under vigorous stirring. Finally, any remaining amount of water was introduced to ensure the required concentration of surfactant. All ingredients were mixed using a magnetic stirrer for 5 minutes to ensure a homogeneous solution. The exemplary compositions were easy to pour and stable over time at room temperature.

[0131] Table 3. Composition of test formulations 3 and 4 and reference formulation 4 used in the environmental stress cracking test. Test formulation 3 / % Test formulation 4 / % Reference formulation 4 / % Rhamnolipid 2.5 0.0 0.0 Sophorolipid 0.0 5.0 0.0 C12-14 fatty alcohol ethoxylate, 6 EO 2.5 2.5 2.5 Water Added to 100% Added to 100% Added to 100%

[0132] Table 4. Composition of test formulations 5 to 8 and reference formulations 5 and 6 used in the environmental stress cracking test Test formulation 5 / % Test formulation 6 / % Test formulation 7 / % Test formulation 8 / % Reference formulation 5 / % Reference formulation 6 / % Rhamnolipid 2.5 2.5 0 0 0 0 Sophorolipid 0 0 5 5 0 0 Linear alkyl benzene sulfonate sodium salt 2.5 0 2.5 0 2.5 0 Alkyl polyglucoside 0 2.5 0 2.5 0 2.5 Water Added to 100% Added to 100% Added to 100% Added to 100% Added to 100% Added to 100%

[0133] The results of the environmental stress cracking are summarized in Table 5. The baseline formulation 4, which contained 2.5 wt% fatty alcohol ethoxylate, caused environmental stress cracking of the bars made from all of the test materials, such as polymethyl methacrylate, polycarbonate, acrylonitrile butadiene styrene, and polystyrene. Surprisingly, the bars exposed to test formulation 3 did not show any damage from environmental stress cracking after 14 days of testing. This result was very surprising because test formulation 3 contained the same amount of fatty alcohol ethoxylate as baseline formulation 4, and additionally 2.5 wt% rhamnolipid. Thus, it is clear that the addition of rhamnolipid to a formulation containing a surfactant, such as fatty alcohol ethoxylate, can prevent the stress cracking effect that the fatty alcohol ethoxylate normally causes on plastic materials.

[0134] No environmental stress cracking was observed in the plastic bars exposed to test formulation 4.

[0135] The same experiment was performed with test formulations 5-8 and baseline formulations 5 and 6, and the results are summarized in Table 6. It can be seen that in the case of bars exposed to test formulations 5-8, which contained combinations of rhamnolipid or sophorolipid, and sodium linear alkyl benzene sulfonate and alkyl polyglycoside, there was no damage from environmental stress cracking after 14 days of testing. This was not the case for formulations containing only sodium linear alkyl benzene sulfonate or alkyl polyglycoside on polycarbonate bars, and only sodium linear alkyl benzene sulfonate on acrylonitrile butadiene styrene.

[0136] Table 5. Environmental stress cracking results after 14 days (Yes - stress cracking observed after completion of test, No - stress cracking not observed after completion of test) Test formulation 3 Test formulation 4 Reference formulation 4 Polymethyl methacrylate No No Yes Polycarbonate No No Yes Acrylonitrile-butadiene-styrene No No Yes Polystyrene No No Yes

[0137] Table 6. Environmental stress cracking results after 14 days (Yes - stress cracking observed after completion of test, No - stress cracking not observed after completion of test) Test formulation 5 Test formulation 6 Test formulation 7 Test formulation 8 Reference formulation 5 Reference formulation 6 Polymethyl methacrylate No No No No No No Polycarbonate No No No No Yes Yes Acrylonitrile-butadiene-styrene No No No No Yes No Polystyrene No No No No No No

[0138] It is readily apparent from the results that biosurfactants, such as rhamnolipid and sophorolipid, are particularly mild to plastic surfaces because they do not cause environmental stress cracking of plastic materials such as polymethyl methacrylate, polycarbonate, acrylonitrile butadiene styrene, and polystyrene. Furthermore, it is clear that biosurfactants can be effectively used in combination with other common surfactants, such as fatty alcohol ethoxylate, to prevent environmental stress cracking caused by aqueous solutions of the surfactants on plastics.

Claims

1. A method for measuring the area of ​​a plastic product, comprising the following steps A) providing a liquid composition comprising a biosurfactant and contacting the article with the liquid composition, and optionally B) at least partially removing said liquid composition comprising said biosurfactant from said preparation.

2. The method according to claim 1, characterized in that The plastic article comprises a polymer selected from acrylic resins, in particular methacrylates and methyl methacrylates, polyamides, polyesters, silicones and polyurethanes, polycarbonates, polyethylene, polypropylene, polystyrene, polyvinyl chloride and polyoxymethylene, preferably selected from polycarbonate, polystyrene and methyl methacrylate, more preferably selected from acrylonitrile butadiene styrene, polycarbonate and polymethyl methacrylate.

3. The method according to claim 1 or 2, characterized in that The biosurfactant is selected from rhamnolipid, glucolipid and sophorolipid, preferably rhamnolipid and glucolipid, and most preferably rhamnolipid.

4. The method according to any one of the preceding claims, characterized in that The liquid composition provided in step A) comprises a non-biological surfactant, preferably selected from anionic, cationic, nonionic, semi-polar, amphoteric and zwitterionic surfactants, especially nonionic surfactants, more preferably selected from fatty alcohol alkoxylates and alkyl polyglucosides, especially fatty alcohol ethoxylates.

5. The method according to any one of the preceding claims, characterized in that The liquid composition provided in step A) comprises a biosurfactant in an amount of 0.1 to 30 wt.-%, preferably 0.5 to 10 wt.-%, more preferably 1.0 to 8 wt.-%, wherein the weight percentages are based on the total liquid composition.

6. The method according to any one of the preceding claims, characterized in that The liquid composition provided in step A) comprises water in an amount of 70% to 99.9% by weight, preferably 90% to 99.5% by weight, more preferably 92% to 99.0% by weight, wherein the percentages by weight are based on the total liquid composition.

7. The method according to any one of the preceding claims, characterized in that The liquid composition provided in step A) comprises the non-biological surfactant in an amount of 0.1 to 30 wt.-%, preferably 0.5 to 10 wt.-%, more preferably 1.0 to 8 wt.-%, wherein the weight percentages are based on the total liquid composition.

8. The method according to any one of the preceding claims, characterized in that The liquid composition provided in step A) comprises a biosurfactant in an amount of 20 to 100 wt.-%, preferably 30 to 70 wt.-%, more preferably 40 to 60 wt.-%, wherein the weight percentages are based on the sum of all surfactants contained in the liquid composition.

9. Use of a biosurfactant for reducing and / or preventing environmental stress cracking of areal-scale plastic articles, preferably environmental stress cracking caused by at least one non-biosurfactant.

10. Use of a biosurfactant for reducing areal-measured signs of aging on plastic articles, preferably induced by at least one non-biosurfactant.

11. The use according to claim 9 or 10, characterized in that The biosurfactant is selected from rhamnolipids, glucose lipids and sophorolipids, preferably rhamnolipids and glucose lipids, and most preferably rhamnolipids.

12. The use according to any one of claims 9 to 11, characterized in that The plastic article comprises a polymer selected from acrylic resins, in particular methacrylates and methyl methacrylates, polyamides, polyesters, silicones and polyurethanes, polycarbonates, polyethylene, polypropylene, polystyrene, polyvinyl chloride and polyoxymethylene, preferably selected from polycarbonate, polystyrene and methyl methacrylate, more preferably selected from acrylonitrile butadiene styrene, polycarbonate and polymethyl methacrylate.

13. The use according to any one of claims 9 to 12, characterized in that The non-biological surfactant is selected from anionic, cationic, nonionic, semi-polar, amphoteric and zwitterionic surfactants, especially nonionic surfactants, more preferably selected from fatty alcohol alkoxylates and alkyl polyglucosides, especially fatty alcohol ethoxylates.

14. The use according to any one of claims 9 to 13, characterized in that The biosurfactant is included in a liquid composition together with the non-biosurfactant.

Citation Information

Patent Citations

  • Use of mixture of glyco-lipid and surfactant in hand dish-washing detergent

    DE19600743A1

  • Skin-friendly washing=up liquid with good cleaning performance

    DE19648439A1

  • cosmetic preparation

    DE2939519A1

  • Inducing rhamno:lipid synthesis in Pseudomonas aeruginosa - with glyceric acid ether lipid, to form intermediate for rhamnose which is used in synthesis of chiral cpds.

    DE4127908A1

  • Method for producing rhamnose

    EP0282942A2